Sistem Pengelompokan Jenis Kaleng Bekas Berdasarkan Model Warna CMYK - Resti, Yulia; Burlian, F.; Fusito, Fusito; Yani, I. (Seminar Nasional Lahan Suboptimal, 2019)
Resti Y, Burlian F, Fusito F, Yani I. 2019. Grouping system of the used cans type based on CMYK color model. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 338-344. Palembang: Unsri Press The automatic sorting process in the recycling industry requires a grouping system. This research aims to build a grouping system of used cans into three types; aluminum, tin plate and aerosols. The grouping is done based on the Cyan, Magenta, Yellow, and BLacK (CMYK) color models of the image of the used cans which are captured using a digital camera when placed on a conveyor belt. The grouping method used is a statistical method based on the Bayes theorem and the assumption of independence on the input variables. The results obtained show that the Naïve Bayes method is able to group used cans by type with an accuracy rate greater than 82%.Keywords: accuracy rate, digital images, naïve bayes